Inclusion, parental involvement and social support: a study on the perceptions of parents and teachers - Felizardo, Sara (2017)
Proposal Information Research on the roles of social support in families of children with special educational needs has been argued that this construct influences directly and indirectly various aspects of parental functioning and family, including parental involvement in the educational process. This study aims to: i) conduct a comparative analysis of groups of parents of children with and without special needs, with regard to the variables of social support and parental involvement in school; ii) understand the relationships between the perspectives of parents and teachers (regular education and special education) about the involvement and participation of parents in school.